The Antimicrobial Peptide Mastoparan X Protects Against Enterohemorrhagic Escherichia coli O157:H7 Infection, Inhibits Inflammation, and Enhances the Intestinal Epithelial Barrier - Zhao, Xueqin; Wang, Lei; Zhu, Chunling; Xia, Xiaojing; Zhang, Shouping; Wang, Yimin; Zhang, Huihui; Xu, Yanzhao; Chen, Shijun; Jiang, Jinqing; Liu, Shanqin; Wu, Yundi; et al. (Frontiers in Microbiology, 2021)
Escherichia coli can cause intestinal diseases in humans and livestock, destroy the intestinal barrier, exacerbate systemic inflammation, and seriously threaten human health and animal husbandry development. The aim of this study was to investigate whether the antimicrobial peptide mastoparan X (MPX) was effective against E. coli infection. In this study, MPX exhibited no toxicity in IPEC-J2 cells and notably suppressed the levels of interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), myeloperoxidase (MPO) and lactate dehydrogenase (LDH) induced by E. coli. In addition, MPX improved the expression of ZO-1, occludin, and claudin and enhanced the wound healing of IPEC-J2 cells. The therapeutic effect of MPX was evaluated in a murine model, revealing that it protected mice from lethal E. coli infection. Furthermore, MPX increased the length of villi and reduced the infiltration of inflammatory cells into the jejunum. SEM and TEM analyses showed that MPX effectively ameliorated the jejunum damage caused by E. coli and increased the number and length of microvilli. In addition, MPX decreased the expression of IL-2, IL-6, TNF-α, p-p38 and p-p65 in the jejunum and colon. Moreover, MPX increased the expression of ZO-1, occludin and MUC2 in the jejunum and colon, improved the function of the intestinal barrier and promoted the absorption of nutrients. This study suggests that MPX is an effective therapeutic agent for E. coli infection and other intestinal diseases, laying the foundation for the development of new drugs for bacterial infections.